Carpenter's and builder's layout, foundation, and framing - Miller, Mark R. (Wiley Pub., 2005)
Here's knowledge you can build onWhether you're building a storage shed or your dream house, the same principles govern choosing a site, setting the foundation, erecting the walls, and putting on the roof. This handy how-to guide has been totally revised and updated to cover new building materials and the latest techniques in construction and framing. It's where to find answers and solutions, from the first stake to the last roofing nail.* Choose an appropriate site and lay out the structure* Construct a foundation that meets structural needs and weather conditions* Work wi.